Verrucous plane xanthomas secondary to lipoprotein X dyslipidemia in the context of cholestatic fulminant hepatitis: A case report - Julie Dang (SAGE Publishing, 2021)
Cutaneous xanthomas are the result of dermal deposition of lipid, mostly caused by disorders of lipid metabolism. Less commonly, they occur in the setting of cholestatic liver disease, leading to accumulation of lipoprotein X, a rare form of dyslipidemia that does not respond well to conventional treatments. We describe an atypical presentation of sudden diffuse xanthomas secondary to lipoprotein X dyslipidemia in the context of cholestatic fulminant hepatitis caused by trimethoprim-sulfamethoxazole hypersensitivity. Histopathology was also atypical and showed an unusual verrucous appearance consisting of overlying epidermal hyperplasia with hyperkeratosis. Our patient had significant improvement, after normalization of her lipid panel under cholestyramine and 13 sessions of apheresis, with topical corticosteroids offering some relief. This rare case shows the importance of recognizing atypical presentations of xanthomas, particularly when they do not respond to conventional dyslipidemia treatments.